Philadelphia Paper - The Late Operations on the Mariposa Estate - Charles M. Rolker (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1879)
The Mariposa estate, a grant made by the Mexican Government to Juan 13. Alvarado, during the time when California was still under the dominion of Mexico, was purchased in 1847 by J. C. Fremont, and the United States patent issued to him in 1856. By sale, or its equivalent, money advanced, the property came into the hands of the Mariposa Company, June 25th, 1863, and through a varied existence of work and temporary inactivity, has as yet been kept as an undivided property, and rests at present with the Mariposa Land and Mining Company of California. I pass over this period of 15 years without giving the history of the ups and downs of the estate, partly because it is familiar to many, and also because I think in such a case this paper would assume too much the character of a narrative. The estate is situated in Mariposa County, California, about 170 miles southeast of San Francisco. It begins in lat. 37' 26' 38'' north, and long. 119' 55' west, and runs 6 miles north; thence 69 miles west; thence 5 miles northwesterly towards the Merced River; thence 84 miles southerly; thence 3 miles easterly; thence 1 mile southerly; thence 2 miles easterly; thence 2 miles southerly; thence 2 miles easterly; thence 1 mile southerly; thence 2 miles easterly; thence 1 mile northerly, and thence 2 miles easterly to the place of the beginning; embracing 44,387 acres (70 sq. miles) more or less. To describe this vast estate in detail as to its full geology, its numerous quartz veins, its many facilities to exploit them and work them by cheap methods, would lead me further than I intend to go at present, and I will content myself to describe the latest workings of the company and its immediate field of operations. As long ago as 1860 the late Dr. Adelberg advised the running of an adit from the northwestern edge of the estate at Benton Mills 011 the Mereed River. His object was to undercut the deepest workings of the then paying mines on the estate—the Pine Tree and Josephine. Following this advice, the tunnel known as "River Tunnel " was commenced. Its entrance is in S. 5, T. 4, s. R. 17 E. It is run in